Three quarters dead - Peck, Richard (Speak, 2011)
Sophomore loner Kerry is overjoyed when three popular senior girls pick her to be in their clique, until a shocking accident sets off a string of supernatural occurrences that become more and more threatening
Keywords: Dead / Fiction; Friendship / Fiction; Horror stories; Dead / Juvenile fiction; Friendship / Juvenile fiction